2014
DOI: 10.1186/1746-6148-10-49
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glutathione, glutathione peroxidase and glutathione S-transferase pi in canine mammary tumors

Abstract: BackgroundGlutathione (GSH) is one of the most important agents of the antioxidant defense system of the cell because, in conjunction with the enzymes glutathione peroxidase (GSH-Px) and glutathione S transferase pi (GSTpi), it plays a central role in the detoxification and biotransformation of chemotherapeutic drugs. This study evaluated the expression of GSH and the GSH-Px and GSTpi enzymes by immunohistochemistry in 30 canine mammary tumors, relating the clinicopathological parameters, clinical outcome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Previous studies have reported that the expression levels of GSH are elevated in numerous types of human cancer tissue, and increased expression levels of GCLC have also been identified in lung, breast, liver, and other types of cancer (19,20). In addition, GCLC and GSS were highly expressed in the mammary tumors and can be used as prognostic markers for mammary neoplasm (21). Furthermore, a previous study demonstrated that drug-resistance is associated not only with elevated GSH levels, but also with increased activity of GCLC (22).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported that the expression levels of GSH are elevated in numerous types of human cancer tissue, and increased expression levels of GCLC have also been identified in lung, breast, liver, and other types of cancer (19,20). In addition, GCLC and GSS were highly expressed in the mammary tumors and can be used as prognostic markers for mammary neoplasm (21). Furthermore, a previous study demonstrated that drug-resistance is associated not only with elevated GSH levels, but also with increased activity of GCLC (22).…”
Section: Discussionmentioning
confidence: 89%
“…[22] reported no significant difference in serum thiol groups in dogs with and without mammary tumor. Increased GSH expression is reported in canine mammary tumors without ulceration, not metastatic tumors, and low mortality [25]. Intracellular GSH maintains the reduced status of thioredoxin which activates ribonucleotide reductase, a key enzyme essential for DNA synthesis [1].…”
Section: Discussionmentioning
confidence: 99%
“…38 Elevated GSH levels have been observed in numerous types of human cancer tissues and increased glutamate-cysteine ligase catalytic activity (GCLC) have also been reported in lung, breast, liver, and other types of cancer. 44 GCLC and GSH synthetase are enzymes in GSH metabolism and their levels were reported to be elevated in CRC tissues. 42 Hence increased GSH metabolism may indicate increased oxidative status in cancer cells due to increased energy metabolism.…”
Section: Discussionmentioning
confidence: 99%